MODEL PENDIDIKAN ISLAM BERBASIS NILAI SEBAGAI UPAYA PENCEGAHAN KONFLIK SOSIAL DI LINGKUNGAN MULTIKULTURAL - Ahmad Fuad Abdul Baqi; Agustin, Maulid (LPPM STAI Muhammadiyah Probolinggo, 2025)
In the context of increasing social conflict and identity-based tensions in multicultural societies, Islamic education holds strategic potential as a preventive instrument. This research seeks to formulate a theoretical model of value-based Islamic education aimed at enhancing students’ emotional intelligence and preventing social conflict. Using a qualitative approach through library research, this study systematically analyzes scholarly literature from 2015 to 2025, focusing on Islamic education, value integration, multiculturalism, and conflict resolution. Data were collected through documentation techniques and analyzed using descriptive-qualitative methods involving thematic categorization and synthesis of conceptual findings. The study highlights four core Islamic values al-‘adl (justice), rahmah (compassion), tasamuh (tolerance), and ukhuwwah (brotherhood) as pillars for shaping inclusive character education. The results indicate that value-based Islamic education strengthens social cohesion and emotional awareness among students. This model contributes not only to the development of a theoretical framework that integrates religious, emotional, and social competencies but also to the design of educational policies that support peaceful and inclusive societies.